Drift pattern of tropical stream insect: understanding the aquatic iinsects movement - Amila Faqhira Z.,; Suhaila A.H., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
An investigation to determine the drift pattern of aquatic insects in an upstream river in Perak, Malaysia was carried out. Drift was sampled by collecting drifting insects using drift sampler at every six hourly intervals within 24-hours period. A total of 3147 individuals of drifting aquatic insects was collected represented by 9 orders, 49 families and 81 genera. There was a significant difference in the temporal drifting pattern in aquatic insects (Kruskal-Wallis test, P =0.00). Greatest drift abundance occurred at night time, which approximately 40 % higher than during the daytime samples, signifying diel periodicity of aquatic insect drift. In addition, nights without moonlight exhibited more drift rate as compared to bright, full-moonlit nights and differed significantly (P<0.05). Drifting aquatic insects displayed alternant pattern with the greatest abundance at 0200 to 0800 h interval, and the least was at 1400 to 2000 h interval.